Evaluación de boldenona y buclizina en el engorde de toretes brown swiss a pastoreo en el cantón Palanda de la provincia Zamora Chinchipe. - Sarango Amay, Jhinpson Andres (2019)
The present investigation was carried out on the estate of Mr. Ángel Girón located in Palanda Canton at a height of 1200 m.a.s.l., with the objective of evaluating the application of Boldenona and Buclizina in the fattening of Brown Swiss bulls under extensive grazing. For this, 24 bulls were used, with which four experimental groups were formed by means of a random block design: T1 (Boldenone), T2 (Boldenone + Buclizine), T3 (Buclizine) and T4 (control). The duration of the experiment was 120 days, variables such as total and daily weight gain were measured, morphometric measurements (height at the withers, body length and thoracic perimeter), blood values (hematocrit and red blood cells) and biochemical values (glucose, HDL and LDL), an economic analysis was carried out by calculating profitability. In weight increase, T1 and T2 stood out with 0.470 and 0.480 kg / day respectively, which are significantly higher (P> 0.05) at T3 and T4 with 0.330 and 0.320 kg / day respectively, in the morphometric variables T1 and T2 also stand out had the greatest increases with respect to T3 and T4, no effects were found on the analyzed blood variables attributable to the drugs used in this investigation. In the economic analysis, the best profitability was obtained with T2 (Boldenona + Buclizina) 49% and T1 (Boldenona) with 45% profitability.